FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN GULA KRISTAL PUTIH DI DAERAH ISTIMEWA YOGYAKARTA - Ecclisia Sulistyowati; Tri Wisudawati; Wahyu Adhi Saputro (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2020)
Sugar serves as a source of energy/calories for the body. The demand for sugar in Region of Yogyakarta has increased along with the increasing population. Consumers have their own criteria for choosing and consuming sugar. This study aims to know and analyze about factors that influence the purchase decision of sugar in DIY. The approach used is descriotive quantitive with a population of sugar consumers who shop at mini markets and super markets in DIY. Determination of sampling using purposive sampling. Respondents numbered as many as 40 people. Data analysis used multiple regression analysis. The results showed that simultaneously of product quality, price, packaging, product and brand guarantees has influence to purchased decision of sugar, but separately the quality, product and brand guarantees has influence, while price and packaging has no influence to purchase decision of sugar in DIY.